Impact of plastic film mulching on global warming in entire chemical and organic cropping systems: Life cycle assessment. (25th July 2021) - Lee, Jeong Gu; Chae, Ho Gyeong; Cho, Song Rae; Song, Hyeon-Ji; Kim, Pil Joo; Jeong, Seung Tak
Abstract: Plastic film mulching (PM) has been exploited as a beneficial cropping tool to control weeds and to improve soil conditions in temperate-monsoon climate regions. However, the impact of PM on global warming is not clearly understood because it can increase both net primary production (NPP) and soil organic matter decomposition. In particular, the additional greenhouse gas (GHG) emissions from the film manufacturing industry and from waste disposal processes have not been properly considered. To investigate the influence of PM on GHG fluxes in the entire cropping system, PM and no-mulching treatments were installed under organic and chemical fertilization treatments for maize cultivation. The net global warming potential (GWP) was determined by using two GHG (CH4 and N2 O) fluxes and soil carbon (C) stock changes with CO2 equivalents within the entire cropping system. PM significantly increased the net GWP by 95 and 35% compared to no-mulching under the organic and chemical fertilization treatments, respectively, whereas most of the net GWP (88–91%) was affected by the GHG flux of the inner cropping boundary. In the cropping process, an average 83 and 91% of the net GWP was influenced by the decrease in the soil C stock in the organic and chemical fertilization treatments, respectively. In contrast, organic fertilization was effective in decreasing the net GWP under the same mulching system due to the reduced soil C stock. PM increased maize grain yield by an average of 52 and 70% compared to no-mulching in the organic and chemical fertilization treatments, respectively, and PM decreased the GHG intensity (GHGI), which implies a net GWP per grain yield of 20 and 30%, respectively, compared to no-mulching. In conclusion, PM can be an effective tool to reduce the GHGI compared to no-mulching; however, PM was more effective in the chemical fertilization treatment than in the organic amendment treatment. Graphical abstract: Image 1